Clinical significance of talon cusp in a mixed dentition patient - Bhuvaneshwari Srinivasan; Anbuselvan Gobichettipalayam Jegatheeswaran; Senthilnathan Radhakrishnan; Faisal Mansour Bin Hayyan; Arthiie Thangavelu (Wolters Kluwer Medknow Publications, 2021)
Talon cusp is a developmental dental anomaly with supernumerary structure projecting from the dento-enamel junction towards the incisal edge of an anterior tooth. The etiology is usually unknown but studies states that talons cusp can occur due to the hyperactivity of the enamel organ during morph differentiation. The incidence is 0.04-10% and the prevalence is more in maxillary incisors than mandibular incisors and more in palatal aspect of the teeth. The most common complications are esthetics, increased risk for caries and occlusal accommodation. This article reports a case of talon cusp on the palatal surface of the permanent maxillary lateral incisor. Due to its clinical significance the dentist should be able to diagnose the supernumerary tooth and definitive treatment should be done.